Academic research management: opportunities vs limitations of incentives - M. V. Niyazova (Russian State Vocational Pedagogical University, 2024)
Introduction. The ongoing academic discourse regarding strategies to enhance academic research highlights the dual impact of different management practices on the quantity and quality of research in higher education. Aim. The article is devoted to analysing the dynamics of academic research results at regional universities, focusing on the opportunities and limitations of stimulating individual scientific productivity. Methodology and research methods. The study widely used a combined approach to gather an array of data on the results of academic research. This systematic approach involves managing the results in combination with statistical, sociological, and comparative research methods. The empirical basis for this study was the data on higher education from 2012 to 2022. The data was sourced from the Federal State Statistics Service of the Russian Federation, which monitors the effectiveness of universities under the Ministry of Science and Higher Education of Russia. Additionally, data was gathered from the Scientific Electronic Library of the Russian Federation, international citation databases, and the results of an online survey conducted among scientific and pedagogical staff at universities in the Russian Federation. Results. In the studied period, universities in the Primorsky Krai of the Russian Federation have shown an increase in visibility within the national scientific community in terms of R&D volume and publication numbers. However, there has been a decline in the academic environment for scientific and pedagogical staff due to increased teaching loads, reduced incentive opportunities compared to the regional standard, and the risk of short-term employment. The heightened intensity and uncertainty have become limiting factors affecting the quality of academic research at individual universities, particularly in terms of the impact factor of the journals where the research results are published. A sociological survey conducted among employees revealed a relatively low level of confidence in the system designed to promote individual scientific productivity. Scientific novelty. The scientific novelty of the study lies in the development of organisational and methodological foundations for managing and assessing academic research within the framework of incentive-based outcomes. Practical significance. The practical significance of the results lies in highlighting trends in the dynamics of academic research at the regional level, illustrating tools to reduce information asymmetry regarding their results. This is achieved by using variables that help identify the limitations of incentives of individual research productivity for its development.